Facial expression of pain in horses undergoing flexion test and relation to lameness - Lindstedt, Ingrid (SLU/Dept. of Clinical Sciences (until 231231), 2017)
SUMMARY Recent studies have indicated that horses in pain exhibit a facial expression of pain. The so called pain face includes a number of different pain specific attributes. Up until now, the equine pain face has only been studied on horses with induced somatic pain or post-operative pain. Subsequently this study aimed to investigate whether the pain face can work as clinical tool in pain assessment of horses undergoing flexion tests in lameness diagnostics. The hypothesis was that horses with positive flexion tests would show pain face during the flexion, whereas horses with negative flexion tests would not show pain face during the flexion. 24 horses were included in the study. All horses showed positive flexion test reactions from at least one joint. The horse faces were filmed during flexion tests as well as when they were not provoked. Three film sequences for each horse was selected for further investigation: a negative flexion test, a positive flexion test and a control sequence. All film sequences were randomized and scored by blinded observers. The observers scored each facial expression as having no pain face, a pain face present or an intense pain face present. No significant difference in the grading of pain face could be seen when comparing positive versus negative flexion tests. The same went for comparing positive flexion tests versus control sequences. The reason for these non-significant findings can be multiple. There might be large individual variations in the expression of pain face in different situations. The result could also indicate that there were several different pathological (and painful) conditions in these horses (chronic or non-chronic) that influenced the face mimic of the horses. Another possible cause for the result could also be that the equine pain scale does not apply very well to horses with orthopedic conditions